Effect of an implanted Walker tumour on metabolism of folic acid in the rat. - Barford, P. A. (Nature Publishing Group, 1978)
The metabolism of 2-[14C] folic acid has been studied in rats with an implanted Walker 256 tumour and in a closely matched group of controls. In animals with tumours, more of the labelled folic acid is converted to 10-formyltetrahydrofolate and 10-formylfolate than in normal animals. No 5-methyltetrahydrofolate could be detected in tumour tissue, or in the livers of tumour-bearing animals. When a mixture of 2-[14C]- and 3',5',9-[3H]-folic acid is given to tumour-bearing rats a similar pattern of metabolites is found. There is apparenly less scission of the folate molecule in tumour-bearing rats than in normal rats.